Diagnostic value of RAS mutations in Bethesda category IV thyroid nodules: a systematic review and meta-analysis - Sun, Jiayue; Hou, Yilin; Sun, Chengfei; Wu, Di; Zhang, Yunfei (Frontiers in Oncology, 2025)
ObjectivesThyroid nodules classified as Bethesda category IV cannot be diagnosed with fine-needle aspiration. RAS mutations have been linked to thyroid cancer, although it is still unclear if they are useful as a pre-operative molecular screening for this particular subgroup. In order to assess the diagnostic accuracy (sensitivity, specificity, AUC, etc.) of RAS mutations in identifying malignancy among Bethesda IV nodules and to ascertain whether this can consistently direct clinical decision-making and minimize non-essential interventions, we carried out a systematic review and meta-analysis using postoperative histopathology as the reference standard.MethodsA literature search of the PubMed, Embase, Cochrane Library, Web of Science and OVID databases was conducted. In all of the included studies, the diagnostic accuracy of RAS was compared with that of postoperative pathology, which was used as a standard. Data were pooled, and the sensitivity, specificity, area under the curve (AUC), positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR) were calculated to estimate the accuracy of RAS.ResultsA total of 10 studies were included after screening, comprising 913 cases of Bethesda Category IV nodules. Among them, there were 246 malignant lesions and 667 benign lesions. The pooled sensitivity of RAS mutations was 0.35 (95% CI, 0.29-0.41), and the specificity was 0.93 (95% CI, 0.90-0.95). The positive likelihood ratio was 3.46 (95% CI, 1.94-6.18), the negative likelihood ratio was 0.73 (95% CI, 0.60-0.89), and the AUC was 0.7954. Heterogeneity testing showed p<0.05, I2 = 58.5%, indicating significant heterogeneity.ConclusionRAS mutations have a moderate diagnostic value in the diagnosis of Bethesda Category IV thyroid nodules. Despite the presence of some heterogeneity, the detection of RAS mutations may be helpful in guiding clinical decision-making and management strategies.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024608197.